Ursula K. Le Guin’s Earthsea and Its Place in the American West’s Literary Landscape - Alkorta, Jon (International Journal of English Studies, 2025)
As a writer that incessantly directed her efforts towards raising her readers’ awareness of social, racial, and gender issues, American writer Ursula K. Le Guin’s fantasy work has been rather overlooked by literary criticism. Thus, the present paper seeks to claim this writer’s prominent position as a writer of the American West, as well as proposing her Earthsea saga as a rightful contribution to the literature of the American West. With this in mind, the paper will argue that Le Guin achieves this by combining elements that belong to the more traditional literature of the West, as is the idea of mobility, with some of the more modern proposals made by the regional perspective of the second half of the past century.